Bayesian informed evidence against modulation of androstadienone-effects by genotypic receptor variants and participant sex: A study assessing Stroop interference control, mood and olfaction - Hornung, Jonas; Noack, Hannes; Thomas, Mara; Farger, Gisbert; Nieratschker, Vanessa; Freiherr, Jessica; Derntl, Birgit (Hormones and Behavior, 2018)
The androgen derivative androstadienone (AND) is present in human sweat and may act as human chemosignal. Though effects of AND have been reported with respect to emotional and cognitive processes, results have been highly inconsistent. For this reason, it is likely that AND-action is dependent on modulatory factors. Here we wanted to specifically investigate the impact of genotypic variations of the AND-receptor OR7D4, as well as the influence of participant sex and concomitant hormonal fluctuations on AND-action during emotional interference processing, olfactory performance and mood assessments.To this end 80 healthy individuals (women taking oral contraceptives; naturally cycling women measured during the luteal phase and men) were tested twice on two consecutive days (AND vs. placebo exposure) with an emotional Stroop task. Also, olfactory performance and mood was assessed. Participants provided saliva samples to measure testosterone, progesterone and estradiol and a blood sample to assess genotypic variations of the AND-receptor OR7D4.We found a small task-dependent reduction of overall error rates under AND but no modulation of effects by genetic variation or group (female OC, female NC, male) with respect to olfactory performance and mood. Additional analyses with help of Bayesian statistics gave strong evidence in favor of specific null hypotheses suggesting that the action of AND was not modulated by either genotypic variations or sex of participants with respect to interference control (bias indices), olfactory self-reports and mood parameters.Additional effects of AND in connection with hormonal fluctuations are reported.
Keywords: Androstadienone; Pheromones; Emotional Stroop task; OR7D4; Sex differences; Oral contraceptives; Menstrual cycle; Sex hormones; Bayesian statistics